130 Immunogenic potential of chimeric antigen receptor (CAR)-engineered T cells expressing inducible nuclease-deactivated SpCas9 (dCas9). (9th November 2020) - Patel, Dharmeshkumar; Patel, Dharmeshkumar; Goswami, Angshumala; Balan, Vitaly; Yang, Zhifen; Li, Lingyu; Rajavel, Sowndharya; Kearney, Alper; Harari-Steinfeld, Rona; Bobbin, Maggie; Wang, Bing; Cesano, Alessandra; et al.
Abstract : Background: The application of CRISPR-Cas9 for personalized medicine is potentially revolutionary for the treatment of several diseases including cancer. However, the bacterial origin of the Cas9 protein raises concerns about immunogenicity. Recent ELISA-based assays detected antibodies against Cas9 from Streptococcus pyogenes (SpCas9) and Staphylococcus aureus (SaCas9) in 5–10% of sera from 343 normal healthy individuals. 1, 2 SpCas9-specific memory CD8 T cell responses were not demonstrated in those individuals. To date, there are no conclusive studies assessing whether CRISPR-Cas9-modified CAR-T could raise CD8 T cell-mediated immunogenicity in humans. Refuge CAR-T cell platform employs an inducible, non-gene editing, nuclease deactivated Cas9 (dCas9) to modulate gene expression in response to external stimuli such as antigen-dependent CAR signaling to suppress PD-1 expression. Methods: In the present study, we analyzed two putative HLA-A*02:01 and two HLA-B*07:02-associated SpCas9 T cell epitopes. The candidate epitopes were derived from a prediction algorithm that incorporates T cell receptor contact residue hydrophobicity and HLA binding affinity. We engaged in-vitro sensitization (IVS) assay to identify immunogenic potential of dCas9 peptides. Results: Autologous IVS assay of T cells in two healthy donor PBMCs identified CD8-T cell responses after two rounds of stimulation against only one HLA-A*02:01-associated Cas9 peptide (sequence NLIALSLGL) P1– while the other candidate epitopes did not elicit any response. Dextramer analysis demonstrated that 15% of CD8+ T cells were specific for P1 and 11% of CD8+ cells produced INFG upon challenge with P1-loaded T2 cells. Conclusions: Our in-vitro sensitization assay was able to demonstrate that dCas9 epitope P1 is immunogenic and may elicit adaptive immune response against gene edited CAR-T cells. Endogenous processing and presentation of P1 and other putative epitopes by Refuge CAR-T cells are currently being analyzed. Acknowledgements: Refuge Biotechnologies Inc. Menlo Park, California, 94025 Trial Registration: N/A Ethics Approval: N/A Consent: N/A References: Simhadri VL, McGill J, McMahon S, Wang J, Jiang H, Sauna ZE. Prevalence of Pre-existing Antibodies to CRISPR-Associated Nuclease Cas9 in the USA Population. Mol Ther Methods Clin Dev 2018;10 :105–112. Published 2018 Jun 15. doi:10.1016/j.omtm.2018.06.006 Ferdosi SR, Ewaisha R, Moghadam F, et al. Multifunctional CRISPR-Cas9 with engineered immunosilenced human T cell epitopes. Nat Commun 2019;10(1):1842. Published 2019 Apr 23. doi:10.1038/s41467-019-09693-x